2009
DOI: 10.1101/lm.1494409
|View full text |Cite
|
Sign up to set email alerts
|

Context representations, context functions, and the parahippocampal–hippocampal system

Abstract: Psychologists and neurobiologists have a long-standing interest in understanding how the context surrounding the events of our lives is represented and how it influences our behavior. The hippocampal formation emerged very early as a major contributor to how context is represented and functions. There is a large literature examining its contribution that on the surface reveals an array of conflicting outcomes and controversy. This review reveals that these conflicts can be resolved by building Nadel and Willne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
311
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(330 citation statements)
references
References 107 publications
(170 reference statements)
16
311
1
2
Order By: Relevance
“…Contextual fear acquisition involves configural or spatial learning [47], and is mediated by the hippocampus [43]. It is well established that fear conditioning to a target tone is mediated by the amygdala [30,33], and conditioning to context is primarily mediated by the hippocampus [44,45,46,49,67]. Thus, the present data supports the hypothesis that GHB in adolescent rats disrupts hippocampal functions.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Contextual fear acquisition involves configural or spatial learning [47], and is mediated by the hippocampus [43]. It is well established that fear conditioning to a target tone is mediated by the amygdala [30,33], and conditioning to context is primarily mediated by the hippocampus [44,45,46,49,67]. Thus, the present data supports the hypothesis that GHB in adolescent rats disrupts hippocampal functions.…”
Section: Discussionsupporting
confidence: 79%
“…Alcohol has been reported to disrupt contextual freezing in young animals, and this alcohol-induced memory deficit is associated with significant CA1 pyramidal neuronal loss [6,35,59]. Some other brain areas that are thought to support contextual fear conditioning include parahippocampal structures [18,46], medial prefrontal cortex [20], medial geniculate nucleus [31], and cerebellum [48].…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that the selective loss of DG granule cells produces a deficit in object memory only when the rat must remember the context in which the object had been previously encountered adds to a converging body of evidence that suggests the hippocampus is essential in storing and retrieving certain types of context memories (Rudy 2009). Specifically, we show that hippocampal granule cells are necessary for supporting associations between objects and contexts.…”
mentioning
confidence: 56%
“…Thus, in those studies that show an involvement of the hippocampus in object recognition, the presence of two different objects in the sample phase might create additional contextual cues or object-object associations that are themselves vulnerable to hippocampal damage. Indeed, previous studies have suggested that the hippocampus can play a role in object recognition if such cues are present (Rudy, 2009;Oliveira et al, 2010). The demonstration that disconnection of the hippocampus from either the perirhinal or medial prefrontal cortex produces significant impairments in the object-in-place task is an important addition to our knowledge of which regions interact during recognition memory tasks involving the integration of object and spatial information.…”
Section: Discussionmentioning
confidence: 98%